Detection of Microsatellite Loci in Rhinoceros Beetle Oryctes Rhinoceros. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2006)

(untitled)
Oryctes Rhinoceros is an economically important pest to the agricultural sector especially to 011 palm industries. Losses of yield due to this pest could reach up to 80% of the crop. Many control techniques have been adopted in the Integrated Pest Management of the beetles. IncludIng the use of pheromone. The pheromone. ethyl 4-methyloctanoate. can attract huge numbers of adults. However. It was observed that not all population of the beetles in the field was attracted to the pheromone. this could be due to the fact that the pheromone substance is very specific and employs a compound unique to certain species.